The history of mathematics a source-based approach - Barrow-Green, June 1953-; Gray, Jeremy J. 1947-; Wilson, Robin J. 1943- (MAA Press, an imprint of the American Mathematical Society, 2019)
Starts with ancient Egypt and Mesopotamia, and continues
Keywords: Geschichte; Mathematics -- History; Mathematics -- Study and teaching; History and biography ... Instructional exposition (textbooks, tutorial papers, etc.); History and biography ... History of mathematics and mathematicians ... General histories, source books; History and biography ... History of mathematics and mathematicians ... Indigenous European cultures (pre-Greek, etc.); History and biography ... History of mathematics and mathematicians ... Egyptian; History and biography ... History of mathematics and mathematicians ... Babylonian; History and biography ... History of mathematics and mathematicians ... Greek, Roman; History and biography ... History of mathematics and mathematicians ... China; History and biography ... History of mathematics and mathematicians ... India; History and biography ... History of mathematics and mathematicians ... Medieval; History and biography ... History of mathematics and mathematicians ... 17th century; Mathematik